2019
DOI: 10.1093/toxsci/kfz064
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Engineered Nanomaterial Inhalation During Gestation Disrupts Vascular Kisspeptin Reactivity

Abstract: Maternal engineered nanomaterial (ENM) inhalation is associated with uterine vascular impairments and endocrine disruption that may lead to altered gestational outcomes. We have shown that nano-titanium dioxide (nano-TiO 2 ) inhalation impairs endothelium-dependent uterine arteriolar dilation in pregnant rats. However, the mechanism underlying this dysfunction is unknown. Due to its role as a potent vasoconstrictor and essential reproductive hormone, we examined how kisspeptin is involved in nano-TiO 2 -induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 39 publications
10
31
1
Order By: Relevance
“…The results of our current study also corroborate data from previous nanotoxicological investigations from our group and others that have shown reduced fetal weight, or restricted fetal growth, after chronic maternal inhalation of nano-titanium dioxide particles [39,52]. We have previously postulated that diminished fetal development after maternal nanoparticle exposure in our studies may be associated with indirect vascular de ciencies leading to uteroplacental ischemia in late-stages of pregnancy [39,53,54].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our current study also corroborate data from previous nanotoxicological investigations from our group and others that have shown reduced fetal weight, or restricted fetal growth, after chronic maternal inhalation of nano-titanium dioxide particles [39,52]. We have previously postulated that diminished fetal development after maternal nanoparticle exposure in our studies may be associated with indirect vascular de ciencies leading to uteroplacental ischemia in late-stages of pregnancy [39,53,54].…”
Section: Discussionsupporting
confidence: 91%
“…The results of our current study also corroborate data from previous nanotoxicological investigations from our group and others that have shown reduced fetal weight, or restricted fetal growth, after chronic maternal inhalation of nano-titanium dioxide particles [39,52]. We have previously postulated that diminished fetal development after maternal nanoparticle exposure is associated with indirect vascular de ciencies leading to uteroplacental ischemia in late-stages of pregnancy [39,53,54].…”
Section: Discussionsupporting
confidence: 91%
“…For engineered NMs, studies in experimental animals indicate that maternal NM exposure during gestation interferes with maternal vascular reactivity and placental vascular development and function. Exposure to NMs has been associated with increased tone and contractility of the uterine vasculature [162][163][164][165][166]. In some studies, placentas from exposed pregnant rats were larger, while their offspring were smaller compared to the control group, indicative of effects downstream from the uterine vascular impairment [163,166].…”
Section: Nm Interference With Vascular Signaling and Utero-placental mentioning
confidence: 99%
“…The study was performed in non-pregnant females, but the mechanisms ought to be also investigated during pregnancy. In another study, inhalation of TiO 2 NPs during pregnancy was found to augment vasoconstriction of the uterine artery in response to Kisspeptin [166]. Kisspeptin is a potent vasoconstrictor and an essential reproductive hormone, which is secreted by the placenta during late pregnancy at 10,000-fold higher levels compared to the non-pregnant state (reviewed in [168]).…”
Section: Nm Interference With Vascular Signaling and Utero-placental mentioning
confidence: 99%
See 1 more Smart Citation